GANGGUAN KEJIWAAN TOKOH UTAMA NOVEL HAGURUMA KARYA AKUTAGAWA RYUUNOSUKE - Fajria Noviana (IZUMI, 2013)
Abstract   This article discusses mental breakdown’s tendency and symptoms of “Haguruma” novel’s main character. The main character is a poet who lived temporarily in a hotel in Tokyo, apart from his family, to finish writing his novel. In that time, he had several symptoms that led him to some kind of mental breakdown’s tendency. The symptoms, for example, are anxiety, drug dependence, hallucination, delusion, paranoia, obsessive, etc. Psychological approach is used to explain and define main character’s mental breakdown, which called schizophrenia. Keywords: main character, psychology, mental breakdown, symptoms